Análise dialógica das polêmicas envolvendo a CNBB nos comentários da rede social Facebook. - Oliveira, Manoel Klebson de Andrade (2020)
The general aim of this research is to analyze how the polemic comments involving the NCBB - National Conference of Bishops of Brazil (CNBB - Conferência Nacional dos Bispos do Brasil) on social media, Facebook are set up. By using the characteristics of this genre which does not have a shape, a content and a fixed structure, we have as specific aim to investigate the types of polemic correlating with the values which these utterances have brought with basis on the extraverbal context and in the linguistic materiality. It’s known that social media has been putting more and more emphasis on daily communication. We have seen in Jakubinskij (2015 [1923]), Volochinov (2013 [1930]; 2017 [1929]) and Bakhtin’s works (1997 [1963]; 2015, [1934 – 1935]; 2016 [1979]; 2017 [1979]) the theoretical and methodological basis to analyze the comments based on the notions of language, dialogism, utterance, discursive genre, polemic as well as contemporary scholars of the dialogical theory of language. The corpus of this research was built of comments about a documentary published on February 23, 2018 on Facebook which accuses the National Conference of Bishops of Brazil of political alliances with the Labor Party (Partido dos Trabalhadores) and their resistance to the doctrine of the Roman Catholic Church. With that being said, we have selected some comments in order to analyze the ideological confrontation between the lay faithful conservative Catholic and the progressives. The result reveals the conflict amongst the different social voices, the social polarization on the Internet, the types of polemics, the verbal violence between the supporters of each position (conservative and progressive) and the inseparability of the religious and politics spheres. Moreover, the analysis shows that this discursive genre works as a dialogue which is shaped by the axiological position of the Internet user.